Comparison of energy consumption between recycle and conventional process of flour milling : at break system - Mustapa Kamal, Siti Mazlina; Webb, C.; Hussain, Siti Aslina (2006)
The amount of energy used for the milling process is an important economical consideration. Increasing the energy usage will increase the operating cost or reduce the mill's profits. The aim of this study is to reduce the usage of energy in a break system of the flour milling process. The strategy was to introduce a recycle grinding circuit in the break system in order to reduce the amount of energy used. A comparison of energy usage the between the recycle and conventional processes at break system of the flour milling was made. However this study has limitations and only concentrated on the calculation of energy used by the main equipments in the break system such as roller mill, sifter, purifier, and bran finisher. With similar target production, 60 tonnes white flour per day, the energy used in recycle process was found to be 713.30 kW and conventional process was 893.01kW. The result showed that the conventional process consumed more energy that was 25% higher compared ti the recycle process. It was concluded that the recycle process successfully reduces energy consumption at the break system compared to the conventional milling process.